Prevalence and pattern of rheumatic valvular heart disease in Africa: Systematic review and meta-analysis, 2015-2023, population based studies. - Seid Mohammed Abdu; Altaseb Beyene Kassaw; Amare Abera Tareke; Gosa Mankelkl; Mekonnen Belete; Mohammed Derso Bihonegn; Ahmed Juhar Temam; Gashaw Abebe; Ebrahim Msaye Assefa (PLoS ONE)
Background Rheumatic heart disease is a global health concern with a persistently high incidence in developing countries, including Africa. It has a significant economic, morbidity, and mortality burden, particularly for children and young adults during their most productive years. However, in the last ten years, the extent of its impact in Africa has remained unclear. Limited studies conducted on the continent have reported diverse prevalence rates of rheumatic heart disease. As a result of these, the study aimed to aggregate and synthesize findings from population-based studies to offer a comprehensive and updated overview of rheumatic heart disease prevalence and pattern at the African level. Methods The studies were identified through a comprehensive literature search of the electronic databases, including PubMed, Google Scholar, Web searches, and manual searches. The descriptive information for the study is presented in the table, and the quantitative results are presented in forest plots. The Cochrane Q test and I2 test statistic were used to test heterogeneity across studies. The pooled estimate of the prevalence of rheumatic heart disease was computed by a random effects model. Results Out of 22 population-based studies analyzed using random-effects, the pooled magnitude of rheumatic heart disease was found to be 18.41/1000 (95% CI: 14.08-22.73/1000). This comprised definite cases of rheumatic heart disease at a prevalence rate of 8.91/1000 (95% CI: 6.50-11.33/1000) and borderline cases at a prevalence rate of 10.69/1000 (95% CI: 7.74-13.65/1000). The combined prevalence of rheumatic heart disease in males was almost equivalent to that in females. Mitral valve regurgitation was the predominant valve affected by rheumatic heart disease, accounting for approximately 73%. Conclusion This study analysis found the prevalence of rheumatic heart disease in Africa is high. Because of this, policies and interventions should give attention to prioritize continuous population based active surveillance for early detection of cases to the reduction of rheumatic heart disease sequel, especially in the children and adolescent population.